Evolution analysis of fistula repairs Cimino-Brescia type arteriovenous at Surgical Clinic B " - Esperón, Alejandro; López Chapuis, Daniel; Dutto, Gabriel; Rojas, María (Cirugía del Uruguay, 1998)
The importance of the making and maintenance of adequate angioaccess has motivated the development of a research fine at Clínica Ouirurgica "8". The aim of this paper is to ana/yse the evo!ution of repairs of arterio-venous fistulas (AVF) of the Cimino-Brescia type performed at our center. 23 repairs carried out in 17 patients were studied.